Seismic damage evaluation of reinforced concrete buildings with slit walls. Issue 6 (3rd August 2015) - Baetu, Sergiu Andrei; Barbat, Alex H; Ciongradi, Ioan Petru; Baetu, Georgeta
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate a reinforced concrete multi-storey building with dissipative structural walls. These walls can improve the behaviour of a tall multi-storey building. The authors' main objective is to evaluate the damage of a building with dissipative walls in comparison with that of a building with solid walls. Design/methodology/approach – In this paper, a comparative nonlinear dynamic analysis between a building with slit walls and then the same building with solid walls is performed by means of SAP2000 software and using a layer model. The solution to increase the seismic performance of a building with structural walls is to create slit zones with short connections in to the walls. The short connections are introduced as a link element with multi-linear pivot hysteretic plasticity behaviour. The hysteretic rules and parameters of these short connections were proposed by the authors and used in this analysis. In this study, the authors propose to evaluate the damage of a building with reinforced concrete slit walls with short connections using seismic analysis. Findings – Using the computational model created by the authors for the slit wall, a seismic analysis of a multi-storey building with slit walls was done. From the results obtained, the advantages of the proposed model are observed. Originality/value – Using a simple computational model, created by the authors, that consume low processing resources and reduces processing time, a nonlinear dynamic analysis on high-rise buildings was done. Unlike other studies on slit walls with short connections, which are focused mostly on the nonlinear dynamic behaviour of the short connections, in this paper the authors take into consideration the whole structural system, wall, connections and frames.